Renin Angiotensin System (RAS) and Immune System Profile in Specific Subgroups with COVID-19 - de Barcelos Ubaldo Martins, Ludimila; Jabour, Luiz Gustavo Pessoa Pires; Vieira, Cristina C.; Nery, Lucas C. C.; Dias, Raphael F.; Simões e Silva, Ana Cristina (Current Medicinal Chemistry, 2021)
Background: The identification of vulnerable subgroups and risk factors associated with the susceptibility to severe acute respiratory syndrome coronavirus 2 (SARS-CoV- 2) infection and coronavirus disease 2019 (COVID-19) is of utmost importance in a pandemic scenario. Potential interactions between renin-angiotensin system (RAS), immune markers and COVID-19 play a role in disease outcome in specific groups of patients. Objective: This review aimed to describe the particularities of the RAS and the immune system profile of particular subgroups of patients. Methods: This non-systematic review summarizes evidence on SARS-CoV-2 infection in specific subgroups of patients and possible relationships between immune system, RAS and the pathophysiology of COVID-19. Results: The RAS and the immune system exert a role in the pathogenesis and prognosis of COVID-19, mainly in cases of hypertension, diabetes, obesity and other chronic diseases. The overactivation of the ACE/Ang II/AT1R axis and the enhancement of inflammation contribute to deleterious effects of COVID-19. Likewise, pregnant women and elderly patients usually display immune responses that are less effective in withstanding exposition to viruses, while children are relatively protected against severe complications of COVID-19. Women, conversely, exhibit stronger antiviral responses and are less sensitive to the effects of increased Ang II. Future Perspectives: The recognition of vulnerable subgroups and risk factors for disease severity is essential to better understand the pandemic. Precision medicine tools, including proteomics and metabolomics approaches, identified metabolic patterns of the severe form of disease and might be the alternative to diagnose, evaluate and predict the prognosis and the efficiency of therapies.
Keywords: SARS-CoV-2